2013
DOI: 10.1098/rspb.2013.1255
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal escape from fungal parasitism in natural communities of anciently asexual bdelloid rotifers

Abstract: Sexual reproduction is costly, but it is nearly ubiquitous among plants and animals, whereas obligately asexual taxa are rare and almost always shortlived. The Red Queen hypothesis proposes that sex overcomes its costs by enabling organisms to keep pace with coevolving parasites and pathogens. If so, the few cases of stable long-term asexuality ought to be found in groups whose coevolutionary interactions with parasites are unusually weak. In theory, antagonistic coevolution will be attenuated if hosts dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…As has consistently been found in other collections of bdelloid rotifers (Birky et al 2005;Fontaneto et al 2009Fontaneto et al , 2011) the phylogeny of the mitochondrial sequences revealed distinct clades, monophyletic groups of individuals with closely related sequences well separated from other groups ( Figure 3). As found in other such bdelloid clades, there is wide geographic dispersion within clades, consistent with the minute size of bdelloids and their ability to survive desiccation and be transported by wind (Wilson and Sherman 2013).…”
Section: Resultsmentioning
confidence: 75%
“…As has consistently been found in other collections of bdelloid rotifers (Birky et al 2005;Fontaneto et al 2009Fontaneto et al , 2011) the phylogeny of the mitochondrial sequences revealed distinct clades, monophyletic groups of individuals with closely related sequences well separated from other groups ( Figure 3). As found in other such bdelloid clades, there is wide geographic dispersion within clades, consistent with the minute size of bdelloids and their ability to survive desiccation and be transported by wind (Wilson and Sherman 2013).…”
Section: Resultsmentioning
confidence: 75%
“…In their natural environments, such as mosses and lichens, A. vaga individuals experiencing desiccation are likely to be exposed to solar UV radiations. In some specific conditions, A. vaga can be exposed to massive UV irradiation, for instance in Arctic or Alpine mosses (Fontaneto & Melone, ; Kaya et al ., ), or when carried by wind at high altitudes (under the form of contracted ‘tun’; Wilson & Sherman, ). Besides such extreme conditions, it is interesting to outline that the relatively mild UV‐A dose used in this study was able to significantly impair A. vaga survival during desiccation.…”
Section: Discussionmentioning
confidence: 97%
“…How then does the Red Queen explain the existence of ancient asexual lineages? Wilson & Sherman (, ) showed that ancient asexuality may be possible in rotifers, because the rotifers can eliminate infections by entering into a desiccated resting stage. In addition, the resting stage is wind‐dispersed, independent of parasites, thus breaking the coevolutionary loop that is critical to the maintenance of sex under the Red Queen (Wilson & Sherman, , ).…”
Section: Tests Of the Red Queen Hypothesis Using Natural Populationsmentioning
confidence: 99%